Development of Learning Materials Integrated of Social Aritmetic and Accounting - Taufik, Mohammad Anang; Mulyoto, Mulyoto; Sunardi, Sunardi; Suryani, Nunuk (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The development of integrated learning materials of social arithmetic and accounting was carried out with the aim of making prototypes of learning materials that integrated social arithmetic and accounting. The development combines social arithmetic material as a calculation process and accounting for the preparation of financial statements. This development uses the ADDIE model. The test of the effectiveness of learning materials as a result of the development was carried out by experimental research using posttest group design. The research subjects were students of Middle School 2 Gondang Bojonegoro East Java class VIII A as the experimental class and class VIII B as the control class. The research subjects consisted of 56 students. 28 students in the experimental class, 28 in the control class. The results of the study show that the learning materials developed are feasible and effective to be used in learning integrated social arithmetic and accounting. The results also showed that there were differences in student learning outcomes in the experimental class and the control class. This can be seen from the value of the average posttest in the experimental class is 95.89 in the control class is 87.67 so that the difference is 8.22.